2009
DOI: 10.1099/vir.0.015990-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective modification of rice (Oryza sativa) gene expression by rice stripe virus infection

Abstract: Rice stripe disease, caused by rice stripe virus (RSV), is one of the major virus diseases in east Asia. Rice plants infected with RSV usually show symptoms such as chlorosis, weakness, necrosis in newly emerged leaves and stunting. To reveal rice cellular systems influenced by RSV infection, temporal changes in the transcriptome of RSV-infected plants were monitored by a customized rice oligoarray system. The transcriptome changes in RSV-infected plants indicated that protein-synthesis machineries and energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
99
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 74 publications
10
99
0
Order By: Relevance
“…3A). It has been reported that RSV infection induced the expression of OsRDR1 in rice (Satoh et al, 2010;Du et al, 2011). As we have shown that RSV infection induced the accumulation of miR444 (Fig.…”
Section: Overexpression Of Mir444 Increases Rice Resistance Against Vsupporting
confidence: 71%
See 2 more Smart Citations
“…3A). It has been reported that RSV infection induced the expression of OsRDR1 in rice (Satoh et al, 2010;Du et al, 2011). As we have shown that RSV infection induced the accumulation of miR444 (Fig.…”
Section: Overexpression Of Mir444 Increases Rice Resistance Against Vsupporting
confidence: 71%
“…The expression of the key factors of RNA-silencing pathways usually is activated by virus infection at the transcriptional level to increase the activities of antiviral RNA silencing. For example, the expression of AGO1, AGO2, or RDR1 was usually induced by infection with diverse viruses (Yang et al, 2004;Alamillo et al, 2006;Zhang et al, 2006;Azevedo et al, 2010;He et al, 2010;Satoh et al, 2010;VĂĄrallyay et al, 2010;Du et al, 2011;Harvey et al, 2011). However, the molecular mechanisms of activation of the expression of these antiviral genes are unknown.…”
Section: Mir444-regulated Nitrate Signaling May Play Roles In the Ricmentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike other known dicot antiviral responses, we found ;30 protein kinases, particularly those in the receptor-like kinase subfamily, which are uniquely altered in both PMV and PMV+SPMV triggered responses in Brachypodium (Mandadi and Scholthof, 2012). This overrepresentation of protein kinases appears to be a unique feature of monocots, as our transcriptome comparisons with the few other reported monocot virus infections, such as maize infected with Rice black-streaked dwarf virus (genus Phytoreovirus) (Jia et al, 2012) and rice infected with Rice stripe virus (genus Tenuivirus) (Satoh et al, 2010), also revealed a higher proportion of upregulated kinases in the respective monocot virus infections. Together, these results suggest that although monocot and dicot plants share some commonalities, they have discrete and unique responses to plant virus infections.…”
Section: The Panicovirus Complex: New Findings In Plant Virology Usinmentioning
confidence: 50%
“…Rice stripe virus (RSV) downregulates CPRGs during infection and disturbs the photosynthesis [23]. The perturbation of photosynthesis by RSV might be caused by the regulation of a special set of miRNAs that target key genes in chloroplast zeaxanthin cycle, which can lead to impaired chloroplast structure and function [35].…”
Section: Introductionmentioning
confidence: 99%